2015
DOI: 10.1111/and.12464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amlodipine on ischaemia/reperfusion injury in the rat testis

Abstract: The aim of this study was to examine the effects of amlodipine (AML) in rat testicular torsion/detorsion damage. In this study, rats were divided into eight groups: (i) sham; (ii) testicular ischaemia, 2 h of ischaemia; (iii) testicular ischaemia/reperfusion (I/R), 2 h of ischaemia followed by 2 h of reperfusion; (iv) ischaemia + AML (5 mg kg(-1)) administered 30 min before ischaemia; (v) ischaemia + AML (10 mg kg(-1)) administered 30 min before ischaemia; (vi) and (vii) I/R + AML (5 mg kg(-1)) and I/R + AML (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The testis is a sensitive tissue to free radical damage. In reduce the damage caused by reactive oxygen species (Dogan et al, 2016).…”
Section: Testicular Ischaemia Reperfusion Caused By Torsion Detorsionmentioning
confidence: 99%
See 1 more Smart Citation
“…The testis is a sensitive tissue to free radical damage. In reduce the damage caused by reactive oxygen species (Dogan et al, 2016).…”
Section: Testicular Ischaemia Reperfusion Caused By Torsion Detorsionmentioning
confidence: 99%
“…(400×) (a) normal spermatozoa; (b) bent tail; (c) coiled tail; (d) abnormal (elongated) head; (e) free head with a very short tail; (f) short tail condition, antioxidant enzymes such as glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD)reduce the damage caused by reactive oxygen species(Dogan et al, 2016). (400×) (a) normal spermatozoa; (b) bent tail; (c) coiled tail; (d) abnormal (elongated) head; (e) free head with a very short tail; (f) short tail condition, antioxidant enzymes such as glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD)reduce the damage caused by reactive oxygen species(Dogan et al, 2016).…”
mentioning
confidence: 99%
“…Dogan et al[79] examined the effect of amlodipine in a rat model of TT injury. They found a significant decrease of TNF and transforming growth factor-beta in the treatment group, decreases in free radicals and increases in antioxidants such as SOD and GSH.…”
Section: Searchmentioning
confidence: 99%
“…The Ca 2+ /Na + channel blockers verapamil, lidocaine and nifedipine ameliorate the effect of I/R (49)(50)(51)(52). Recently, it was demonstrated that amlodipine decreases free radical levels and increases the levels antioxidants including SOD and GSH (14).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Testes are sensitive to free radical damage. Under normal conditions, enzymatic antioxidant defence systems, including glutathione peroxidase (GPx), superoxide dismutase (SOD) and catalase (CAT), protect those cells from free radical damage (14). During tIR, alterations in cellular and mitochondrial Ca 2+ (mCa…”
Section: Introductionmentioning
confidence: 99%